Guinea pig kille - Graves, Annie; McElhinney, Glenn (Minneapolis Darby Creek, 2015)
When Sandy neglects to take care of his teenaged sister Dolly's guinea pig, Princess Snowflake, while Dolly is away, the beloved pet dies but returns to seek vengeance
Originally published: Dublin, Ireland : Little Island, 2011
Marsa
5 18 22
Keywords: Brothers and sisters -- Fiction; Ghosts -- Fiction; Horror stories